The Value of Cranial CT Imaging in Patients With Headache at the Emergency Department - Lemmens, Cynthia M. C.; van der Linden, M. Christien; Jellema, Korné (Frontiers in Neurology, 2021)
Background: Headache is among the most prevalent complaints in patients presenting to the emergency department (ED). Clinicians are faced with the difficult task to differentiate primary (benign) from secondary headache disorders, since no international guidelines currently exist of clinical indicators for neuroimaging in headache patients. Methods: We performed a retrospective review of 501 patients who presented at the ED for headache over a ten-month period. We determined the use of diagnostic imaging, yield of performed imaging and clinical factors correlated with abnormal CT results. Results: About half of patients were diagnosed with a primary headache disorder. Cranial CT imaging at the ED was regularly performed (61% of patients) and led to diagnosis of underlying pathology in one in 7.6 patients. In the multivariate model, factors associated with abnormal cranial CT results were age 50 years or older, presentation within one hour after headache onset, clinical history of aphasia and focal neurological deficit at examination. Conclusions: As separate clinical characteristics have limited value in detecting severe underlying headache disorders, cranial imaging is regularly performed in the ED. Clinical prediction tools for detecting intracranial pathology in headache patients will help clinicians to reduce cranial imaging in the future.